Bronchial Artery Embolization - Lorenz, Jonathan; Sheth, Deepa; Patel, Jay (Seminars in Interventional Radiology, 2012)
Hemoptysis represents a significant clinical entity with high morbidity and potential mortality. Most hemorrhages from a bronchial source arise in the setting of chronic inflammatory diseases. Medical management (in terms of resuscitation and bronchoscopic interventions) and surgery have severe limitations in these patient populations. Embolization procedures represent the first-line treatment for hemoptysis arising from a bronchial arterial source. This article discusses anatomical and technical considerations, as well as outcomes and complications, in the setting of bronchial arterial embolization in the treatment of hemoptysis.
Keywords: interventional radiology; embolization; bronchial artery; hemoptysis